Filmes e ensino de física: concepções de futuros professores sobre a utilização de seriados de ficção científica - Sorensen, Rafael do Nascimento (2024)
Physics education has often been criticized for its expository, fragmented approach that is disconnected from other areas of knowledge. Considering this, the present dissertation investigates the pedagogical potential of using science fiction (SF) series in teaching Physics. Given the challenges the subject faces in engaging students, this study aims to explore how undergraduates from a federal higher education institution, future Physics teachers, perceive the use of SF series as a teaching strategy for the subject. The general objective was to investigate the proposals for using SF series in Physics classes by these future teachers. Eight undergraduate students from a federal public university in the interior of São Paulo state participated in this qualitative, exploratory research. Data were collected through questionnaires and lesson plans developed by the participants. The results reveal that most participants recognize the potential of SF as a teaching aid, especially in promoting cognition and developing critical and creative skills. However, they highlight the need for pedagogical mediation, with the teacher taking an active role in contextualizing and explaining the scientific concepts present in the narratives. The research points to significant potential in integrating SF series into Physics classes, provided that this strategy is accompanied by proper planning. It is concluded that the investigated approach has the potential to make Physics education more dynamic and engaging, as well as to stimulate students' critical thinking. However, the study's limitations, such as the small number of participants, indicate the need for further research to validate the results in different educational contexts.